Alteration of behavior in mice by muscimol is associated with regional electroencephalogram synchronization. - Vyazovskiy, V; Tobler, I; Winsky-Sommerer, R (2007)
We tested the hypothesis that the effects of GABAergic agonists on behavior and the electroencephalogram (EEG) result from an increased regional synchronization in cortical circuits. The relationship between regional EEG topography, EEG synchronization and alteration of behavior was investigated by administering male C57BL/6 mice (n=7) a high, 3 mg/kg i.p. dose of muscimol, a selective GABA(A) agonist. Parietal and frontal cortical EEG, electromyogram, infrared and running wheel activity were recorded for 3 h before and 9 h after injection. Muscimol consistently elicited biphasic behavioral changes. Initially, it induced a catalepsy-like state lasting 96.0+/-12.4 min. This state was followed by a hyperactivity period of 49.7+/-5.4 min, during which the mice engaged in vigorous wheel running. During catalepsy, the EEG exhibited high amplitude waves which showed a consistent phase relationship between the frontal and parietal derivation. Moreover, the typical regional differences between the EEG spectra of the two derivations were abolished, and a redistribution of EEG power toward lower frequencies (<3 Hz) occurred in both derivations. In contrast, during hyperactivity the parietal EEG was dominated by theta-activity (7-9 Hz), which is typical for running behavior, while high amplitude slow waves, resembling the normal non-rapid eye movement sleep EEG pattern, predominated in the frontal EEG. The data indicate that the GABAergic system is involved in the regulation of cortical synchronization of neuronal activity and suggest a link between regional EEG synchronization and behavioral states.